Discriminating between mothers' infant- and adult-directed speech: Cross-linguistic generalizability from Japanese to Italian and German. (August 2018) - Sulpizio, Simone; Kuroda, Kaori; Dalsasso, Matteo; Asakawa, Tetsuya; Bornstein, Marc H.; Doi, Hirokazu; Esposito, Gianluca; Shinohara, Kazuyuki
Highlights: IDS and ADS can be correctly discriminated by a machine algorithm. Algorithm performs equally well in different languages (Japanese, Italian, German). Algorithm overcomes previous approaches in discriminating between IDS and ADS. Abstract: The aim of the present work was a cross-linguistic generalization of Inoue et al.'s (2011) algorithm for discriminating infant- (IDS) vs. adult-directed speech (ADS). IDS is the way in which mothers communicate with infants; it is a universal communicative property, with some cross-linguistic differences. Inoue et al. (2011) implemented a machine algorithm that, by using a mel-frequency cepstral coefficient and a hidden Markov model, discriminated IDS from ADS in Japanese. We applied the original algorithm to two other languages that are very different from Japanese – Italian and German – and then tested the algorithm on Italian and German databases of IDS and ADS. Our results showed that: First, in accord with the extant literature, IDS is realized in a similar way across languages; second, the algorithm performed well in both languages and close to that reported for Japanese. The implications for the algorithm are discussed.